Evaluation of emergency medical services staff knowledge in breaking bad news to patients. Issue 6 (June 2020) - Rasmus, Paweł; Kozłowska, Elżbieta; Robaczyńska, Katarzyna; Pękala, Krzysztof; Timler, Dariusz; Lipert, Anna
Objective: The aim of the study was to investigate knowledge of breaking bad news (BBN) among medical personnel in the emergency medical services (EMS). Methods: A cross-sectional survey was conducted of 148 individuals employed in EMS. An interview was conducted using a structured questionnaire. Results: Of study participants, 89.2% were not aware of any formal BBN procedure and 58.1% had not participated in any form of training. Compared with males, females were more likely to report that dealing with the emotional state of the family or the patient was the most difficult aspect of BBN. Only a few participants were aware of the SPIKES protocol for BBN, and none knew what the acronym meant. Sex, educational level, occupation, work experience and workplace were not associated with knowledge of BBN procedures. Conclusions: Knowledge of BBN in both male and female EMS staff was insufficient. EMS personnel held different opinions about the method of BBN. Even staff who have participated in specific BBN training or have extensive professional experience were pessimistic about BBN skills in self-assessments.